Oral Corrective Feedback (OCF) and Writing Feedback toward Teachers’ Beliefs - Masrul, Masrul; Asilestari, Putri (LPPM Universitas Pancasakti Tegal, 2023)
Teachers’ view influences the concepts that teachers teach in the classroom. This study examined the correlation between EFL writing feedback and oral corrective feedback (OCF) toward teachers' beliefs. Data were analyzed by the correlation test. The participants were 100 students from Malang State University (50 females and 50 males, with an average age of 19–22). The findings of this research reveal that the relationship between oral corrective feedback and writing feedback on teacher belief is significant and positive. Oral corrective feedback and writing feedback are effective in the teaching and learning. The results of this study can be used as a reference in applying OCF and writing feedback in the classroom. Teachers' beliefs are crucial and should be considered as one of the success factors for students in learning foreign languages.